Parental socio-demographic influences on school-aged children's diets: a comprehensive study in the Republic of Moldova (One Health & Risk Management, 2024)
Introduction. The transition from childhood to adulthood significantly impacts overall health and requires adequate nutrition to facilitate physical and cognitive development. Managing children’s weight and fostering an environment that promotes healthy eating habits are significantly influenced by parents’ knowledge, attitudes, and practices. Material and methods. In February – March 2023, a quantitative study was conducted, involving 472 parents of school-aged children. The questionnaire, developed according to the Knowledge, Attitudes, and Practices methodology, was completed both online, in electronic format, and on paper.Results. The results of the KAP study regarding the nutrition of school-aged children show that parents have a significant level of knowledge (76.9±19.07%) about their children’s nutrition. Regarding attitude, the score is moderate (59.99±10.7%), indicating that parents may not prioritize healthy eating habits for their children or may not be sufficiently motivated to act. However, there is a low level of practice: 45.43±16.6%. Statistical analysis indicates significant correlations between: gender and knowledge (τ=0.175, p
Keywords: knowledge; attitudes; practices; parents; children's nutrition; nutritional education